Nhận thức và thực hành của giáo viên mầm non trong hỗ trợ ngôn ngữ cho trẻ có nền tảng ngôn ngữ đa dạng - Đinh Thanh Tuyến, Đinh Thanh Tuyến; Đào Thái Hà, Đào Thái Hà; Trần Thị Mỹ Dung, Trần Thị Mỹ Dung; Nguyễn Thị Hồng Nhung, Nguyễn Thị Hồng Nhung (Tạp chí Giáo dục, 2026)
In the context of Vietnamese early childhood education, which isincreasingly focused on inclusiveness and the cultural and linguistic diversity of children, supporting language development for children with diverse language backgrounds is becoming an important educational practice. This article surveys how early childhood teachers in Vietnam perceive and implement language support activities for children with diverse language backgrounds, including ethnic minority children and bilingual children. Data was collected through in-depth interviews and classroom observations at several early childhood education institutions in the North and South. The analysis results show four main themes: (1) teachers often perceive linguistic diversity primarily through the level of Vietnamese language use by children; (2) common supportstrategies include language games,storytelling, and flexible code switching; (3) organizing activities is still difficult due to large class sizes, lack of bilingual learning materials, and limitations in professional training; (4) The linguistic diversity context encourages teachers to adjust their pedagogical practices. This article clarifies the practice of supporting language development in preschool education in Vietnam and suggests strengthening teacher training and support policies that align with learners’ cultural and linguistic contexts.